2015
DOI: 10.1002/alr.21671
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of pneumatization of the paranasal sinuses: a comprehensive and validated metric

Abstract: The APPS score is the first comprehensive and validated metric for quantifying the degree of paranasal sinus pneumatization and anatomic variation. This has important potential utility in standardizing evaluation of sinus CT and researching the relationship of sinus pneumatization with clinical parameters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 21 publications
(36 reference statements)
0
15
0
1
Order By: Relevance
“…However, sinus augmentation procedures are not only technique sensitive but are also prone to complications if a thorough preoperative evaluation is not performed. 13 14 15 16 17 In developing any treatment plan for rehabilitation of the edentulous posterior maxilla with implant-supported prostheses, sound knowledge of the anatomy and common variations, patency, and health of the maxillary sinus must be carefully considered. Diagnostic imaging with traditional two-dimensional (2D) radiographic methods using panoramic radiographs and intraoral radiographs plays a crucial role but does not yield three-dimensional (3D) information of the area of interest.…”
Section: Introductionmentioning
confidence: 99%
“…However, sinus augmentation procedures are not only technique sensitive but are also prone to complications if a thorough preoperative evaluation is not performed. 13 14 15 16 17 In developing any treatment plan for rehabilitation of the edentulous posterior maxilla with implant-supported prostheses, sound knowledge of the anatomy and common variations, patency, and health of the maxillary sinus must be carefully considered. Diagnostic imaging with traditional two-dimensional (2D) radiographic methods using panoramic radiographs and intraoral radiographs plays a crucial role but does not yield three-dimensional (3D) information of the area of interest.…”
Section: Introductionmentioning
confidence: 99%
“…Michael et al (11) proposed a score for standardization of variants of pneumatisation using 18 items called Assessment of pneumatisation of paranasal sinuses score (APSS). In our study the pneumatisation identified were that of superior turbinate, crista galli, anterior clinoid process, lateral recess, hard palate , pterygoid plates, and nasal septum.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, volumetric or dimensional analysis of sinus CT tends to be too cumbersome for the large populations that may be necessary to detect small differences [6]. The Assessment of Pneumatization of the Paranasal Sinuses (APPS) score was recently validated for Sinusitis 2016, 1, 92-98 93 evaluating the extent of sinus pneumatization [9,10]. The APPS score evaluates for the presence of nine anatomic variants bilaterally (Table 1, Figure 1), and can be used for clinician assessment of paranasal sinus pneumatization.…”
Section: Introductionmentioning
confidence: 99%
“…This method of determining the extent of sinus pneumatization has not been previously applied to CF or CRS patients. evaluating the extent of sinus pneumatization [9,10]. The APPS score evaluates for the presence of nine anatomic variants bilaterally (Table 1, Figure 1), and can be used for clinician assessment of paranasal sinus pneumatization.…”
Section: Introductionmentioning
confidence: 99%